Applied Mathematics in Ferroelectricity and Piezoelectricity - Uchino, Kenji (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This textbook "Applied Mathematics in Ferroelectricity and Piezoelectricity" was authored to provide the reader solid mathematical background for studying "ferroelectricity and piezoelectricity", as a supplemental reference to my three course books; "Ferroelectric Devices 2nd Edition (2010)", "Micromechatronics 2nd Edition (2019)", and "FEM and Micromechatronics with ATILA Software (2008)", all published from CRC Press. "Physics" prefers "simplicity"; converting a complicated phenomenon expressed by a function.